Ethnopharmacy Study of Herbal Medicine as Antihypertension in Simbang District - Selpida Handayani; Abd. Malik; Nurul Ilmi Mufidah; Risda Waris; Virsa Handayani; Reski Amriati Syarif; Dedy Putra Wahyudi (Faculty of Pharmacy, Universitas Muslim Indonesia, 2022)
Empirically, the Indonesian people have used medicinal plants to cure various diseases. Ethnopharmaceutical studies were carried out as an effort to maintain knowledge of medicinal plants in the community, especially in Simbang District. This study aims to obtain data and information related to medicinal plants used as antihypertensives by the community in Simbang District, Maros Regency. This study was a survey study using a descriptive observational method where sampling uses purposive sampling techniques through interviews and questionnaire distribution. The results obtained were 17 species, 15 families and 16 genera that were used as antihypertensives. Plant parts used as antihypertensives were leaves, fruits, seeds, rhizomes and tubers. The way to use antihypertensive medicinal plants by the community in Simbang District was to be eaten and drunk by processing boiled, brewed, grated and ground.